Diamond thin films integrated with flexible substrates and their physical, chemical and biological characteristics. (9th July 2021) - Xie, Yang; Wang, Huachun; Cheng, Dali; Ding, He; Kong, Deying; Li, Lizhu; Yin, Lan; Zhao, Guanlei; Liu, Lei; Zou, Guisheng; Wei, Junjun; Li, Chengming; et al.
Abstract: Diamond has attracted tremendous attention in materials science and engineering, owing to its superior mechanical, thermal, electrical and optical properties. However, its applications in biomedical fields are constrained by its mechanical rigidity, high temperature fabrication and difficulties of integration with flexible platforms. In this paper, we develop a facile process to form large-area, freestanding diamond thin films and combine them with optoelectronic devices on flexible substrates. Obtained undoped diamond (UD) and boron doped diamond (BDD) films are comprehensively investigated, in terms of their structural, morphological, optical and electrochemical characteristics. On flexible substrates, electrically conductive BDD films are employed as an electrochemical sensor for dopamine detection in aqueous solutions, while optically transparent and thermally conductive UD films can effectively promote heat dissipation of microscale light-emitting diodes. Finally, in vitro cytotoxicity study demonstrates the desirable biocompatibility of these diamond films. The presented techniques remove barriers in the manufacturing and heterogeneous integration of freestanding thin-film diamond materials, and provide promising paths to their broad applications in flexible biointegrated systems.